Community Behavior in The Use of Jampersal in Jember Regency (Phenomenological at Puskesmas Gladak Pakem and Puskesmas Mumbulsari) - Ita Roossinta; Sebastiana Viphindrartin; Iwan Dewanto (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Based on data on the high maternal mortality rate in Jember from 2016-2020 and the lack of utilization of Jampersal in Jember district. This study aimed to determine the predisposing characteristics in the utilization of jampersal in Jember Regency among postpartum women. This study used qualitative research with a phenomenological approach conducted in Jember Regency. Thirty-four research subjects were obtained from the general population of Jember Regency, consisting of maternity women and married men aged 18-45. Research data collection with in-depth interviews. Data analysis using Interpretative Phenomenological Analysis technique. Triangulation of sources was used to obtain the validity of research data. The results showed high predisposing characteristics were associated with jampersal utilization in postpartum women based on demographic, cultural, knowledge, and perception perspectives. The demographic perspective found differences in the selection of health facilities in urban and rural areas. Furthermore, from a cultural perspective, it was found that the practice of traditional birth attendance was related to beliefs. The knowledge perspective found that good knowledge can be optimized in the early detection of emergencies. Furthermore, it was found that there was a misperception in the community when managing the Jampersal requirements. Future researchers need to examine other aspects related to the Jampersal program.